OSYP MAKOVEJ’S NATIONAL IDEA (DEDICATED TO 159 YEARS SIHCE BIRTHDAY) - Макаровський, І. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the content and characteristic features of writer Osyp Makovey’s activity.